PENGARUH NET WORKING CAPITAL, PROFITABILITY, GROWTH OPPORTUNITY, BOARD SIZE TERHADAP CASH HOLDING - Jessica Lim; Yanti Yanti (Jurnal Paradigma Akuntansi, 2023)
This study was done to analyze the effect of Net Working Capital, Profitability, Growth Opportunity, and Board Size on Cash Holdings with Firm Size and Leverage as controlling variables. This study uses secondary data obtained from financial statements and annual report of manufacturing firms listed on IDX for the period 2016-2019. Research method used was multiple linear regression and tested with E-views 12 and SPSS 17. This study uses Generalized Least Square with Random Effect Model selected for testing the hypotesis. Samples are selected with purposive sampling method. Samples are 66 manufacturing companies listed on IDX for the period 2016-2019 with total of 264 data used as samples. This study found that Net Working Capital and Profitability have a positive and significant effect on Cash Holding. While Growth Opportunity and Board Size were found to have no significant effect on Cash Holding.